Sperner's Lemma with Multiple Labels - Bapat, R. B. (Modeling, Computation And Optimization, 2009)
An analogue of Sperner's lemma with multiple, unrestricted labels is proved. It extends a result due to Hochberg, McDiarmid and Saks obtained in the context of determining the bandwidth of the triangulated triangle.